MEDIASTINAL BRONCHOGENIC CYST - Elahi, Sofia; Fecher, Alison; Bridas, Thomas (Journal of Ayub Medical College Abbottabad, 2004)
A 29 year old woman was found to have a chest mass as part of routine screening with a chest x-ray for an unrelated neurosurgical procedure. Further investigation with a chest CT raised the suspicion of a paravertebral neurogenic tumor. The patient underwent bronchoscopy and resection of the lesion by Video Assisted Thoracic Surgery (VATS). The diagnosis of Bronchogenic Cyst was established after histopathologic examination of the resected tumor. Bronchogenic Cysts are relatively rare primary mediastinal tumors. The paravertebral site is an unusual presentation for these tumors.